Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal element, polymer, and method for producing the same

A ring-closed polymer structure with specific structural units addresses thermal decomposition issues in liquid crystal alignment films, ensuring stable alignment and improved heat resistance, even with thin films.

JP7605027B2Active Publication Date: 2024-12-24JSR CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021092614
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-01
Publication Date
2024-12-24
Estimated Expiration
2041-06-01

AI Technical Summary

Technical Problem

Existing liquid crystal alignment films face issues with thermal decomposition during film formation, leading to impurities and reduced electrical properties, especially when the film thickness becomes thin due to poor coating, and there is a need for improved heat resistance and uniformity in liquid crystal alignment.

Method used

The introduction of a ring-closed polymer structure with high heat resistance and a high conversion rate, incorporating specific structural units and compounds to enhance the stability and alignment properties of the liquid crystal alignment film, even when the film thickness is reduced.

Benefits of technology

The proposed solution ensures high reliability in heat resistance and maintains good liquid crystal alignment, reducing thermal decomposition and AC afterimages, even when the film thickness is compromised.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605027000001
    Figure 0007605027000001
  • Figure 0007605027000002
    Figure 0007605027000002
  • Figure 0007605027000003
    Figure 0007605027000003
Patent Text Reader

Abstract

To provide a liquid crystal alignment agent with which a liquid crystal alignment film can be formed which has high reliability on heat resistance and also exhibits excellent liquid crystal alignment properties even if the film thickness of the liquid crystal alignment film becomes smaller owing to a coating defect and the like.SOLUTION: A liquid crystal alignment agent contains a polymer (P) which has at least one kind selected from the group consisting of structure units represented by the formulas (1) to (5). In the formulas (1) to (5), one of X1 and X2 is a univalent group represented by the formula (6), and the other is -OR4. R4 is a hydrogen atom or a univalent organic group with C1 or larger. A1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. In the formula (6), R1 is a hydrogen atom or a univalent organic group with C1 or larger. R2 is an alkanediyl group. R3 is a univalent organic group with C1 or larger.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a liquid crystal aligning agent, a liquid crystal alignment film, a liquid crystal device, a polymer, and a method for producing the same. [Background technology]

[0002] Polyimide is generally used as the polymer component of the liquid crystal alignment film because of its high heat resistance. On the other hand, polyimide has low solubility in solvents, and therefore, when a relatively large hydrophobic group (mesogen structure, etc.) is introduced into the polymer side chain, the solubility is insufficient, and it is considered that the coatability is reduced. Therefore, as an alternative to polyimide, it has been proposed to use acrylic polymers or styrene-maleimide polymers as materials for the liquid crystal alignment film (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 074547 Summary of the Invention [Problem to be solved by the invention]

[0004] Liquid crystal elements are used in a wide range of applications, from LCD TVs to small display devices such as smartphones and tablet PCs. As their applications become more diverse, liquid crystal elements are expected to be operated for longer periods of time and to be used under harsher temperature conditions. Furthermore, as liquid crystal elements become more highly precise, there is a demand for higher coating uniformity, and liquid crystal alignment films that can stably exhibit good liquid crystal alignment properties even when the film becomes thin due to poor coating, etc.

[0005] A liquid crystal alignment film is usually formed on a substrate by applying a liquid crystal alignment agent in which a polymer component is dissolved or dispersed in a solvent onto the substrate and heating at a high temperature (for example, 200 to 250°C). On the other hand, if the heat resistance of the polymer component is insufficient, the polymer component may be thermally decomposed by the heat treatment during film formation, and the components generated by the thermal decomposition may become impurities, resulting in a decrease in reliability, such as a decrease in electrical properties. From the viewpoint of further improving quality in recent years, it is required that the liquid crystal alignment agent has few decomposition products due to heating during film formation and can maintain its performance even when the liquid crystal element is driven for a long time, that is, has high reliability in terms of heat resistance, and can form a liquid crystal alignment film that exhibits good liquid crystal alignment even when the film thickness is thin due to poor coating or the like.

[0006] The present invention has been made in consideration of the above circumstances, and has as its main object to provide a liquid crystal alignment agent which has high reliability in terms of heat resistance and is capable of forming a liquid crystal alignment film having good liquid crystal alignment properties even when the thickness of the liquid crystal alignment film becomes thin due to poor coating or the like. [Means for solving the problem]

[0007] In order to solve the above problems, the present inventors have focused on introducing a structure into the polymer component of a liquid crystal alignment agent that converts into a closed ring structure that is highly heat-resistant when heated during film formation, has a high conversion rate to the closed ring structure, and is less likely to cause a reverse reaction. Specifically, the present invention employs the following means to solve the above problems.

[0008] [1] A liquid crystal aligning agent comprising a polymer (P) having at least one selected from the group consisting of a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), a structural unit represented by the following formula (3), a structural unit represented by the following formula (4), and a structural unit represented by the following formula (5). [ka] (In formulas (1) to (5), X 1 and X 2 one of which is a monovalent group represented by the following formula (6), and the other is -OR4 R 4 A is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. m is 1 or 2. "*1" represents a bond bonded to an atom constituting the main chain of the polymer. [ka] (In formula (6), R 1 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 2 is an alkanediyl group. 3 is a monovalent organic group having one or more carbon atoms. "*" represents a bond.)

[0009] [2] A liquid crystal alignment film formed using the liquid crystal alignment agent of [1] above. [3] A liquid crystal element comprising the liquid crystal alignment film according to [2] above. [4] A polymer having at least one selected from the group consisting of a structural unit represented by the above formula (1), a structural unit represented by the above formula (2), a structural unit represented by the above formula (3), a structural unit represented by the above formula (4), and a structural unit represented by the above formula (5).

[0010] [5] A method for producing a polymer, comprising: a step of reacting a polymer (x) having a structural unit derived from at least one compound selected from the group consisting of a compound represented by the following formula (11), a compound represented by the following formula (12), a compound represented by the following formula (13), and a compound represented by the following formula (14), with a compound (y) represented by the following formula (15): and a step of reacting a reaction product of the polymer (x) and the compound (y) with an esterifying agent. [ka] (In formula (11), n ​​is 0 or 1. In formula (13) and formula (14), A 1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. m is 1 or 2. [ka] (In formula (15), R 1 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 2 is an alkanediyl group. 3 is a monovalent organic group having one or more carbon atoms. Effect of the Invention

[0011] A liquid crystal alignment agent containing the above polymer (P) can form a liquid crystal alignment film that has high reliability in terms of heat resistance and stably exhibits good liquid crystal alignment properties even when the thickness of the liquid crystal alignment film is thin due to poor coating or the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Matters related to the aspects of the present disclosure will be described in detail below. In this specification, the term "hydrocarbon group" includes chain-shaped hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-shaped hydrocarbon group" refers to a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure and are composed only of a chain structure. However, they may be saturated or unsaturated. The term "alicyclic hydrocarbon group" refers to a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, it is not necessary to be composed only of an alicyclic hydrocarbon structure, and it also includes those that have a chain structure as a part of it. The term "aromatic hydrocarbon group" refers to a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, it is not necessary to be composed only of an aromatic ring structure, and it may include a chain structure or an alicyclic hydrocarbon structure as a part of it. The term "main chain" of a polymer refers to the longest "trunk" part of the atomic chain of the polymer. The term "side chain" of a polymer refers to a part branched from the "trunk" of the polymer. The term "organic group" refers to an atomic group formed by removing any hydrogen atom from a carbon-containing compound (i.e., an organic compound).

[0013] Liquid crystal alignment agent The liquid crystal aligning agent of the present disclosure contains the following polymer (P). Polymer (P): A polymer having at least one structural unit (hereinafter also referred to as "structural unit U1") selected from the group consisting of a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), a structural unit represented by the following formula (3), a structural unit represented by the following formula (4), and a structural unit represented by the following formula (5). [ka] (In formulas (1) to (5), X 1 and X 2 one of which is a monovalent group represented by the following formula (6), and the other is -OR 4 R 4 A is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. m is 1 or 2. "*1" represents a bond bonded to an atom constituting the main chain of the polymer. [ka] (In formula (6), R 1 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 2 is an alkanediyl group. 3 is a monovalent organic group having one or more carbon atoms. "*" represents a bond.) Hereinafter, each component contained in the liquid crystal aligning agent of the present disclosure and other components that are optionally blended as necessary will be described.

[0014] <Polymer (P)> (Structural unit U1) In the above formulas (1) to (5), X 1 and X 2 One of the groups is a monovalent group represented by the above formula (6). In the above formula (6), R 1 The monovalent organic group having 1 or more carbon atoms represented by the formula (I) is preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms, more preferably an alkyl group or phenyl group having 1 to 6 carbon atoms, and even more preferably an alkyl group having 1 to 3 carbon atoms. 1 Of these, the group represented by the formula (I) is preferably a hydrogen atom or a methyl group.

[0015] R 2 The alkanediyl group represented by the formula (I) may be either linear or branched. From the viewpoint of obtaining a liquid crystal element that can maintain its performance even when driven for a long time (i.e., has high long-term heat resistance) and has good AC image retention characteristics, R 2 Among them, R is preferably a group that bonds to the nitrogen atom in the above formula (6) via a methylene group (-CH-). 2 is preferably a linear alkanediyl group having 1 to 5 carbon atoms, more preferably a linear alkanediyl group having 1 to 3 carbon atoms, and further preferably a methylene group or an ethylene group.

[0016] R 3 The monovalent organic group represented by the formula (I) is a monovalent hydrocarbon group having 1 to 20 carbon atoms, and any methylene group in the monovalent hydrocarbon group is -O-, -S-, -CO-, -COO-, -NR 10 -, -NR 10 -CO-, -NR 10 A monovalent group having 1 to 20 carbon atoms substituted with one or more selected from the group consisting of -COO- and -N=N- (hereinafter referred to as "monovalent group R E "), a hydrocarbon group or a monovalent group R E Examples of the hydrogen atom of R include a monovalent group having 1 to 20 carbon atoms in which any hydrogen atom of R has been substituted with a fluorine atom, a hydroxyl group, a cyano group, a carboxyl group, or the like, and a monovalent group having a heterocycle. 10 R is a hydrogen atom or a monovalent organic group. 10 Examples of the monovalent organic group represented by the formula (1) include an alkyl group having 1 to 6 carbon atoms, a phenyl group, a tert-butoxycarbonyl group, and a hydroxyalkyl group.

[0017] R 3 It is particularly preferable that the monovalent organic group represented by the formula (I) is a group containing at least one functional group selected from the group consisting of a basic group, a group that generates a basic group when heated, an acidic group, a group that generates an acidic group when heated, a crosslinkable group, a group that generates a crosslinkable group when heated, a photoalignment group, a vertical alignment group, a photoinitiator group, an electron transport group, and a hole transport group.

[0018] Basic groups and groups that generate basic groups when heated R 3 When the monovalent organic group represented by the formula (I) has a basic group and a group that generates a basic group by heating, the basic group can be a nitrogen-containing group. Specific examples of the nitrogen-containing group include a primary amino group, a secondary amino group, a tertiary amino group, and a nitrogen-containing heterocyclic group. 3 Specific examples of the monovalent organic group represented by the formula (r1-1) to (r1-4) that has a basic group and a group that generates a basic group upon heating include groups represented by the following formulas (r1-1) to (r1-4). [ka] (In formulae (r1-1) to (r1-4), PG is a monovalent thermally labile group. "*" represents a bond.)

[0019] The group represented by the above formula (r1-2) generates a basic group by eliminating the group PG upon heating. In the process of forming a liquid crystal alignment film by applying a liquid crystal alignment agent to a substrate and heating it, the group PG is eliminated, and from the viewpoint of simplifying the process, the group PG is preferably a group that decomposes at a temperature of 120 to 300°C and is replaced with a hydrogen atom. Specifically, a tert-butoxycarbonyl group (Boc group) or a 9-fluorenylmethoxycarbonyl group is preferred, and a tert-butoxycarbonyl group is particularly preferred.

[0020] Acidic groups and groups that generate acidic groups when heated R 3 In the case where the monovalent organic group represented by the formula (I) has an acidic group or a group that generates an acidic group upon heating, examples of the acidic group include a carboxylic acid group, a phosphoric acid group, a phosphorous acid group, a sulfonic acid group, and an amic acid group. 3 The acidic group contained in R is preferably a carboxylic acid group or an amic acid group. 3Preferred specific examples of the monovalent organic group represented by the formula (r2-1) to (r2-4) below include groups represented by the formula (r2-2) and (r2-3) below. [ka] (In formula (r2-1) ~ formula (r2-4), R 11 is a hydrogen atom or an alkyl group. PG is a monovalent thermally detachable group. "*" represents a bond.)

[0021] The groups represented by the above formula (r2-2) and formula (r2-4) generate an acidic group by elimination of the group PG upon heating. Examples of the group PG include a group bonded to the oxygen atom in the above formula (r2-2) or the nitrogen atom in the above formula (r2-4) via a tertiary carbon atom. Specific examples include a tert-butyl group, a 1-cyclopentylethyl group, a 1-cyclohexylethyl group, a 1-norbornylethyl group, and a 1-phenylethyl group.

[0022] Crosslinkable groups and groups that generate crosslinkable groups when heated R 3 When the monovalent organic group represented by the formula (I) has a crosslinkable group and a group that generates a crosslinkable group by heating, examples of the crosslinkable group include a (meth)acryloyl group, an alkenyl group, a vinylphenyl group, a β-hydroxyamide group, a furyl group, an epoxy group, a cyclic carbonate group, an alcoholic hydroxyl group, a phenolic hydroxyl group, an isocyanate group, a protected isocyanate group, a trialkoxysilyl group, and a maleimide group. 3 Specific examples of the monovalent organic group represented by the formula (r3-1) to (r3-9) below include those having a crosslinkable group and a group that generates a crosslinkable group upon heating. [ka] (In formulas (r3-1) to (r3-9), R 12 R is a hydrogen atom or an alkyl group. 13is a hydrogen atom or a methyl group. "*" represents a bond.)

[0023] Photo-alignment groups The photo-orientable group refers to a functional group capable of imparting anisotropy to a film by a photoreaction such as a photoisomerization reaction, a photodimerization reaction, a photo-Fries rearrangement reaction, or a photodecomposition reaction caused by irradiation with light.

[0024] Specific examples of the photo-alignment group include an azobenzene-containing group containing azobenzene or a derivative thereof as a basic skeleton, a cinnamic acid structure-containing group containing cinnamic acid or a derivative thereof (cinnamic acid structure) as a basic skeleton, a chalcone-containing group containing chalcone or a derivative thereof as a basic skeleton, a benzophenone-containing group containing benzophenone or a derivative thereof as a basic skeleton, a coumarin-containing group containing coumarin or a derivative thereof as a basic skeleton, a cyclobutane-containing structure containing cyclobutane or a derivative thereof as a basic skeleton, a stilbene-containing group having stilbene or a derivative thereof as a basic skeleton, a phenylbenzoate-containing group containing phenylbenzoate or a derivative thereof as a basic skeleton, etc. Among these, the photo-alignment group is preferably at least one selected from the group consisting of an azobenzene-containing group, a cinnamic acid structure-containing group, a chalcone-containing group, a stilbene-containing group, a cyclobutane-containing structure, and a phenylbenzoate-containing group, and is particularly preferably a cinnamic acid structure-containing group or an azobenzene-containing group in terms of high sensitivity to light and ease of introduction into a polymer.

[0025] Specific examples of the photoalignable group include groups represented by the following formulae (r4-1) to (r4-4). [ka] (In formulas (r4-1) to (r4-4), R is a hydrogen atom or a monovalent organic group. X 3 is -O- or -NH-. "*" represents a bond.)

[0026] Vertically oriented group The vertical alignment group is a group that exhibits the property of vertically aligning liquid crystal molecules without light irradiation, and is a group that imparts a pretilt angle to the liquid crystal. Specific examples of the vertical alignment group include an alkyl group having 3 to 30 carbon atoms, a fluorine-containing alkyl group having 3 to 30 carbon atoms, an alkoxy group having 3 to 30 carbon atoms, a group represented by the following formula (9), and a group having 17 to 51 carbon atoms and a steroid skeleton. [ka] (In formula (9), A 1 ~A 3 R is each independently a phenylene group or a cyclohexylene group, and may have a substituent on the ring portion. 21 is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms in which at least one hydrogen atom is substituted with a fluorine atom, an alkoxy group having 1 to 20 carbon atoms in which at least one hydrogen atom is substituted with a fluorine atom, or a fluorine atom; R 22 and R 23 are each independently a single bond, -O-, -COO-, -OCO-, or an alkanediyl group having 1 to 3 carbon atoms. k, m, and n are integers of 0 or more satisfying 1≦k+m+n≦4. R 21 When represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a fluorine atom, k+m+n≧2 is satisfied. "*" represents a bond.)

[0027] Specific examples of the group represented by the above formula (9) include, but are not limited to, the groups represented by the following formulae (r5-1) to (r5-7). 1 ~A 3 Examples of the substituent that may be present on the ring portion include a fluorine atom, an alkyl group having 1 to 3 carbon atoms, and an alkoxy group having 1 to 3 carbon atoms. [ka] (In formulae (r5-1) to (r5-7), R represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a fluoroalkyl group having 1 to 20 carbon atoms. "*" represents a bond.)

[0028] Photoinitiator group The photoinitiator group is a site that generates polymerization initiation ability by light or a site that has a photosensitizing effect, and is a group having a structure derived from a compound (photoinitiator) that can initiate polymerization of a polymerizable component by irradiation with radiation such as visible light, ultraviolet light, far ultraviolet light, electron beams, and X-rays. The photoinitiator group is preferably a group having a structure derived from a radical polymerization initiator that can generate radicals by irradiation with light. Specific examples of the photoinitiator group include groups having a structure derived from a compound containing a radical generating group, such as an alkylphenone compound, a benzoin compound, a ketal compound, an acetophenone compound, a benzophenone compound, a thioxanthone compound, and an anthraquinone compound.

[0029] Specific examples of the photoinitiator group include groups represented by the following formulas (r6-1) to (r6-11). [ka] (In formulas (r6-1) to (r6-11), R represents a hydrogen atom or an alkyl group. "*" represents a bond.)

[0030] Electron transport groups and hole transport groups Examples of the electron transporting group include groups having a ring structure such as an imidazole ring, a pyridine ring, a pyrazine ring, an oxadiazole ring, a triazine ring, a triazole ring, an oxazole ring, an isoxazole ring, a thiazole ring, an isothiazole ring, a thiadiazole ring, a quinoxaline ring, a quinoline ring, or an isoquinoline ring. Examples of the hole transporting group include groups having an aromatic amine structure (such as a triphenylamine structure or a diphenylamine structure), a carbazole ring, or a thiophene ring.

[0031] X1 and X 2 The other is -OR 4 R 4 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. R is advantageous in that the liquid crystal alignment is stable even when the liquid crystal alignment film becomes thin due to poor coating or the like, and the occurrence of AC image retention can be sufficiently reduced. 4 is preferably a monovalent organic group having one or more carbon atoms. As the monovalent organic group, R 3 Examples of the monovalent organic group represented by the formula R 4 When R is a monovalent organic group having one or more carbon atoms, it is preferable in that it can suppress the elimination of the above formula (6) due to a reverse reaction during post-baking, and the occurrence of AC image retention can be suppressed even when the liquid crystal alignment film becomes a thin film. It is also preferable in that it can ensure phase separation when other polymers are contained in the liquid crystal alignment agent together with the polymer (P). Among these, from the viewpoint of the structural stability of the side chain, R 4 is preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms.

[0032] Of the above formulas (1) to (5), the above formula (1) is a compound having two groups "-CO-X 1 " and the group "-CO-X 2 " has a specific isomeric structure, and the two groups are on the same side. In contrast, the above formulas (2) to (5) have two groups "-CO-X 1 " and the group "-CO-X 2 " isomeric structure.

[0033] From the viewpoint of heat resistance and ease of introduction of the group represented by the above formula (6) into the side chain, the polymer (P) is preferably a polymer having a structural unit derived from a monomer having a polymerizable carbon-carbon unsaturated bond. The type of the monomer having a polymerizable carbon-carbon unsaturated bond constituting the polymer (P) is not particularly limited, and examples thereof include maleic anhydride compounds, (meth)acrylic compounds, aromatic vinyl compounds, maleimide compounds, olefin-based hydrocarbons, and cycloolefin-based hydrocarbons. "*1" in the above formulas (1) to (5) is preferably a bond bonded to a carbon atom constituting the main chain of the polymer.

[0034] The content of the structural unit U1 in the polymer (P) is preferably 5 mol% or more, more preferably 10 mol% or more, based on the total structural units constituting the polymer (P). The content of the structural unit U1 in the polymer (P) is preferably 90 mol% or less, more preferably 80 mol% or less, based on the total structural units constituting the polymer (P). When the content of the structural unit U1 is in the above range, the voltage retention rate can be kept high even when heating is performed for a relatively long time during film formation, afterimages are unlikely to occur even when the thickness of the liquid crystal alignment film is thinned due to poor coating or the like, and the effect of improving long-term heat resistance can be sufficiently obtained, which is preferable.

[0035] (Other structural units) The polymer (P) may be a polymer consisting of only the structural unit U1, but may also have other structural units different from the structural unit U1 in addition to the structural unit U1. As the other structural units, structural units not having the structural unit represented by the above formula (6) can be used. Specifically, a structural unit U2 having a cyclic carbonate structure; -COOR 5 (However, R 5 is a monovalent thermally detachable group); and a structural unit U4 derived from a monomer selected from the group consisting of a compound represented by the following formula (8-1), a compound represented by the following formula (8-2), an N-substituted aromatic maleimide compound, an olefinic hydrocarbon, and a compound that generates an isocyanate group upon heating.

[0036] Structural unit U2 When the polymer (P) has the structural unit U2, an epoxy group can be generated by heating (preferably in the process of forming a liquid crystal alignment film by applying a liquid crystal alignment agent to a substrate and heating it). This generated epoxy group functions as a crosslinkable group, which is advantageous in that it can further improve the long-term heat resistance of the obtained liquid crystal element.

[0037] The structural unit U2 is preferably a structural unit derived from a monomer having a polymerizable carbon-carbon unsaturated bond and a cyclic carbonate group. Specific examples thereof include structural units represented by the following formulae (10-1) to (10-3). [ka] (In formulas (10-1) to (10-3), R 21 , R 22 and R 23 R is each independently a hydrogen atom or a monovalent organic group. 24 is a hydrogen atom or a methyl group. 1 is an oxygen atom or -NH-. 1 is a single bond or a divalent linking group. n1 is 0 or 1. n2 is an integer of 0 to 2.

[0038] The content of the structural unit U2 in the polymer (P) is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total structural units constituting the polymer (P). The content of the structural unit U2 in the polymer (P) is preferably 60 mol% or less, more preferably 55 mol% or less, based on the total structural units constituting the polymer (P). When the content of the structural unit U2 is within the above range, it is preferable in that the thermal decomposition of the polymer can be sufficiently suppressed during the heat treatment at the time of film formation, that afterimages are unlikely to occur even when the film thickness of the liquid crystal alignment film is thinned due to poor coating or the like, and that the effect of improving long-term heat resistance can be sufficiently obtained. The polymer (P) may have only one type of structural unit U2, or may have two or more types.

[0039] Structural unit U3 When the polymer (P) has the structural unit U3, a carboxyl group can be generated by heating (preferably in the process of forming a liquid crystal alignment film by applying a liquid crystal alignment agent to a substrate and heating it). This generated carboxyl group functions as a crosslinkable group, which is preferable in that it can further improve the long-term heat resistance of the obtained liquid crystal element.

[0040] Group “-COOR 5 Specific examples of "X-1" include a structure represented by the following formula (X-1), an acetal ester structure of a carboxylic acid, and a ketal ester structure of a carboxylic acid. [ka] (In formula (X-1), R 31 , R 32 and R 33 is the following (i) or (ii): (i)R 31 , R 32 and R 33 are each independently an alkyl group having 1 to 10 carbon atoms or a monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms. (ii) R 31 and R 32 are combined with each other. 31 and R 32 R represents an alicyclic hydrocarbon structure or a cyclic ether structure having 4 to 20 carbon atoms, which is formed together with the carbon atom to which it is bonded. 33 is an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms. "*" represents a bond.)

[0041] Specific examples of the structure represented by the above formula (X-1) include a tert-butoxycarbonyl group, a 1-cyclopentylethoxycarbonyl group, a 1-cyclohexylethoxycarbonyl group, a 1-norbornylethoxycarbonyl group, a 1-phenylethoxycarbonyl group, a 1-(1-naphthyl)ethoxycarbonyl group, a 1-benzylethoxycarbonyl group, and a 1-phenethylethoxycarbonyl group.

[0042] Specific examples of the acetal ester structure of carboxylic acid include a 1-methoxyethoxycarbonyl group, a 1-ethoxyethoxycarbonyl group, a 1-propoxyethoxycarbonyl group, a 1-butoxyethoxycarbonyl group, a 1-cyclohexyloxyethoxycarbonyl group, a 2-tetrahydropyranyloxycarbonyl group, a 1-phenoxyethoxycarbonyl group, a 2-tetrahydrofuranyloxycarbonyl group, and a 2-tetrahydropyranyloxycarbonyl group.

[0043] Specific examples of the ketal ester structure of carboxylic acid include a 1-methyl-1-methoxyethoxycarbonyl group, a 1-methyl-1-ethoxyethoxycarbonyl group, a 1-methyl-1-propoxyethoxycarbonyl group, a 1-methyl-1-butoxyethoxycarbonyl group, a 1-methyl-1-cyclohexyloxyethoxycarbonyl group, a 2-(2-methyltetrahydrofuranyl)oxycarbonyl group, a 2-(2-methyltetrahydropyranyl)oxycarbonyl group, a 1-methoxycyclopentyloxycarbonyl group, and a 1-methoxycyclohexyloxycarbonyl group.

[0044] The structural unit U3 is a polymerizable carbon-carbon unsaturated bond and a group "-COOR 5 Specifically, the structural units include those represented by the following formulae (7-1) to (7-3). [ka] (In formulas (7-1) to (7-3), R 41 , R 42 and R 43 R is each independently a hydrogen atom or a monovalent organic group. 44 is a hydrogen atom or a methyl group. 2 is an oxygen atom or -NH-. 2 R is a single bond or a divalent linking group. 5 is a monovalent thermally detachable group. m1 is 0 or 1.

[0045] The content of the structural unit U3 in the polymer (P) is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total structural units constituting the polymer (P). The content of the structural unit U3 in the polymer (P) is preferably 65 mol% or less, more preferably 60 mol% or less, based on the total structural units constituting the polymer (P). When the content of the structural unit U3 is within the above range, it is preferable in that the polymer can be sufficiently prevented from thermally decomposing when heated during film formation, that afterimages are unlikely to occur even when the thickness of the liquid crystal alignment film is thinned due to poor coating or the like, and that the effect of improving long-term heat resistance can be sufficiently obtained. The polymer (P) may have only one type of structural unit U3, or may have two or more types.

[0046] Structural unit U4 The polymer (P) may contain a structural unit U4 (excluding the structural units U1, U2 and U3) derived from a monomer selected from the group consisting of a compound represented by the following formula (8-1), a compound represented by the following formula (8-2), an N-substituted aromatic maleimide compound, an olefinic hydrocarbon, and a (meth)acrylic compound that generates an isocyanate group upon heating. By containing the structural unit U4 in the polymer (P), the thermal stability of the side chain can be further ensured, which is advantageous in that the effect of improving the long-term heat resistance of the obtained liquid crystal element can be further enhanced. [ka] (In formula (8-1), R 18 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. 1 R is a divalent aromatic ring group. 19 is a hydrogen atom or a monovalent organic group. 6 is a monovalent substituent. t is an integer of 0 to 3. r is 0 or 1.

[0047] Regarding the compound represented by the above formula (8-1), Ar 1The aromatic ring group represented by the formula (I) is a group obtained by removing two hydrogen atoms from a substituted or unsubstituted aromatic ring. Examples of the aromatic ring include an aromatic hydrocarbon ring and an aromatic nitrogen-containing heterocycle. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring. Examples of the aromatic nitrogen-containing heterocycle include a pyridine ring and a piperazine ring. R 19 Examples of the monovalent organic group represented by the formula (I) include a monovalent hydrocarbon group having 1 to 20 carbon atoms, and a monovalent organic group having a mesogenic structure and having 6 to 30 carbon atoms. R 18 is preferably a hydrogen atom, a group having 1 to 5 carbon atoms, or a phenyl group.

[0048] Specific examples of the compound represented by the above formula (8-1) include styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 5-t-butyl-2-methylstyrene, divinylbenzene, trivinylbenzene, t-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethyl ether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-t-butylstyrene, 3-t-butylstyrene, 4-t-butylstyrene, diphenylethylene, vinylnaphthalene, 4-vinylpyridine, and the following formulae (8-1-1) and (8-1-2): [ka] (In formula (8-1-1) and formula (8-1-2), R 20 is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an alkoxy group having 1 to 20 carbon atoms. and the like.

[0049] Examples of the olefinic hydrocarbon include ethylene, propene, butene, pentene, etc. Examples of the compound represented by the above formula (8-2) include norbornene, methylnorbornene, etc.

[0050] The N-substituted aromatic maleimide compound is a compound in which the hydrogen atom bonded to the nitrogen atom in maleimide is substituted with a monovalent organic group having an aromatic ring. Examples of the aromatic ring include a benzene ring and a naphthalene ring, and these rings may have a substituent. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a halogen atom, and a carboxy group.

[0051] Specific examples of the N-substituted aromatic maleimide compound include N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(4-ethylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-benzylmaleimide, N-naphthylmaleimide, and N-(4-carboxyphenyl)maleimide.

[0052] Examples of the (meth)acrylic compound that generates an isocyanate group upon heating include a reaction product of (meth)acroyloxyethyl isocyanate and diethyl malonate, a reaction product of (meth)acroyloxyethyl isocyanate and 3,5-dimethylpyrazole, and a reaction product of (meth)acroyloxyethyl isocyanate and methyl ethyl ketoxime.

[0053] The content of the structural unit U4 in the polymer (P) is preferably 1 mol% or more, more preferably 2 mol% or more, and even more preferably 5 mol% or more, based on the total structural units constituting the polymer (P). The content of the structural unit U4 in the polymer (P) is preferably 50 mol% or less, more preferably 40 mol% or less, based on the total structural units constituting the polymer (P). When the content of the structural unit U4 is within the above range, it is preferable in that the long-term heat resistance can be improved while maintaining good electrical properties, etc. The polymer (P) may have only one type of structural unit U4, or two or more types.

[0054] The polymer (P) may further contain, as other structural units, structural units different from the structural units U2 to U4, in addition to the above. Examples of the other structural units include (meth)acrylic acid alkyl esters, (meth)acrylic acid esters having an alicyclic structure, (meth)acrylic acid esters having an aromatic ring structure, and conjugated diene compounds. The content of these structural units is preferably 30 mol % or less, and more preferably 25 mol % or less, based on the total structural units constituting the polymer (P).

[0055] (Synthesis of Polymer (P)) The polymer (P) can be obtained by reacting a polymer containing a structural unit having a maleic anhydride structure with a primary or secondary amine having a partial structure represented by the above formula (5) as a reactive compound. More specifically, the polymer (P) can be produced by a method including the following step A. Step A: A step of reacting a polymer (x) having a structural unit U5 derived from at least one compound selected from the group consisting of a compound represented by the following formula (11), a compound represented by the following formula (12), a compound represented by the following formula (13), and a compound represented by the following formula (14) (hereinafter also referred to as an "acid anhydride group-containing compound") with a compound represented by the following formula (15): [ka] (In formula (11), n ​​is 0 or 1. In formula (13) and formula (14), A 1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. m is 1 or 2. [ka] (In formula (15), R 1 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 2 is an alkanediyl group. 3 is a monovalent organic group having one or more carbon atoms.

[0056] ·Acid anhydride group-containing compounds In the synthesis of the polymer (x), a monomer containing an acid anhydride group-containing compound is polymerized to obtain a polymer having a maleic anhydride structure. Preferable specific examples of the acid anhydride group-containing compound include the compounds represented by the following formulas (16-1) to (16-9). [ka]

[0057] The acid anhydride group-containing compound used in the synthesis of the polymer (x) is particularly preferably the compound represented by each of the above formulae (16-1), (16-3) to (16-8), because it has a defined stereostructure and is easy to form an imide ring by post-baking, thereby making it possible to obtain a polymer (P) having excellent long-term heat resistance and side chain structural stability. In addition, in the synthesis of the polymer (x), the acid anhydride group-containing compound may be used alone or in combination of two or more.

[0058] ·Compound(y) Compound (y) is preferably a primary or secondary amine having the functional group. Specific examples of compound (y) include compounds represented by the following formulas (17-1) to (17-28). In producing polymer (P), compound (y) may be used alone or in combination of two or more. [ka] [ka] [ka] [ka]

[0059] The synthesis method of the polymer (x) is not particularly limited, and can be carried out according to a standard method of organic chemistry. When the polymer (x) is produced by a radical polymerization method, the polymerization reaction is preferably carried out in an organic solvent in the presence of a polymerization initiator. As the polymerization initiator to be used, for example, an azo compound such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), or 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) is preferable. The proportion of the polymerization initiator to be used is preferably 0.01 to 30 parts by mass with respect to 100 parts by mass of the total monomers to be used in the reaction. As the organic solvent to be used, for example, alcohol, ether, ketone, amide, ester, hydrocarbon compound, etc. can be mentioned.

[0060] In the above polymerization reaction, the reaction temperature is preferably 30°C to 120°C, and the reaction time is preferably 1 to 36 hours. The amount of organic solvent (a) used is preferably such that the total amount of monomers (b) used in the reaction is 0.1 to 60 mass% relative to the total amount of the reaction solution (a+b). The reaction solution in which the polymer is dissolved can be isolated using a known isolation method, for example, a method in which the reaction solution is poured into a large amount of poor solvent and the resulting precipitate is dried under reduced pressure, or a method in which the reaction solution is distilled under reduced pressure using an evaporator.

[0061] The polymer (x) can be produced by known polymerization methods such as ring-opening metathesis polymerization (ROMP) and polymerization using a metallocene catalyst, in addition to radical polymerization, depending on the type of monomer used.

[0062] The reaction between the polymer (x) and the compound (y) is preferably carried out in an organic solvent, and if necessary, in the presence of a catalyst. Examples of the catalyst include, but are not limited to, pyridine derivatives such as N,N-dimethylaminopyridine, and tertiary amines such as triethylamine. When a catalyst is used, the proportion of the catalyst used is preferably 0.01 to 0.5 molar equivalents relative to the total amount of the structural unit U5 contained in the polymer (x).

[0063] The proportion of compound (y) used is preferably 10 molar parts or more, more preferably 30 molar parts or more, and even more preferably 50 molar parts or more, based on 100 molar parts of the total amount of structural units U5 contained in polymer (x). The proportion of compound (y) used is preferably 200 molar parts or less, more preferably 150 molar parts or less, based on 100 molar parts of the total amount of structural units U5 contained in polymer (x). Compound (y) may be used alone or in combination of two or more kinds.

[0064] Examples of the organic solvent used in the above reaction include alcohols, ethers, ketones, amides, esters, and hydrocarbon compounds. The reaction temperature of the above reaction is preferably 30°C to 120°C, and the reaction time is preferably 1 to 24 hours. In this way, a solution in which the polymer (P) is dissolved is obtained. The reaction solution may be used to prepare a liquid crystal alignment agent after isolating the polymer (P) contained in the reaction solution using a known isolation method.

[0065] ·Process B The polymer (P) may be a polymer produced by step A, or may be a polymer produced by a method including the following step B in addition to step A. By incorporating a polymer produced by the method including step B into a liquid crystal aligning agent, the structural stability of the side chain can be further enhanced, which is preferable in that a liquid crystal element having excellent long-term heat resistance can be obtained. Step B: A step of reacting the reaction product of the polymer (x) and the compound (y) with an esterifying agent

[0066] The esterification agent is not particularly limited as long as it is a compound capable of esterifying the carboxyl group generated in the side chain by the reaction of the polymer (x) with the compound (y). In terms of being able to efficiently carry out esterification, the esterification agent is preferably, among others, diazomethane, trimethylsilyldiazomethane, a mixture of boron trifluoride and an alcohol, a compound represented by the following formula (16), a compound represented by the following formula (17), or a compound represented by the following formula (18). [ka] (In formula (16), R 7 is a hydrogen atom or a methyl group. 8 and R 9 Each of R is independently a monovalent organic group. 10 ~R 12 R is each independently a monovalent organic group. 13 is a hydrogen atom or a monovalent organic group. 14 , R 15 and R 16 R is each independently a monovalent organic group. 17 is a hydrogen atom or a monovalent organic group.

[0067] R in the above formula (16) 8 and R 9 , R in Eq. (17) 10 ~R 12 , and R in formula (18) 13 ~R 16 Examples of the monovalent organic group represented by the formula (I) include a monovalent chain hydrocarbon group, a monovalent alicyclic hydrocarbon group, a group in which any hydrogen atom in a monovalent chain hydrocarbon group or alicyclic hydrocarbon group is substituted with a hydroxyl group or a carboxyl group, and a group in which any methylene group in a monovalent chain hydrocarbon group or alicyclic hydrocarbon group is substituted with a carbonyl group, an amide group, a urea bond or a urethane bond.

[0068] Specific examples of the compounds represented by the above formulas (16) to (18) include the compounds represented by the following formulas (20-1) to (20-5), respectively. [ka]

[0069] The reaction between the reaction product of the polymer (x) and the compound (y) and the esterification agent is preferably carried out in an organic solvent. The organic solvent is preferably a solvent capable of dissolving or dispersing the reaction product and the esterification agent. The reaction temperature is preferably 0 to 80°C, more preferably 10 to 60°C. The reaction time is, for example, 30 minutes to 12 hours.

[0070] The weight average molecular weight (Mw) of the polymer (P) in terms of polystyrene measured by gel permeation chromatography (GPC) is preferably 1,000 to 300,000, more preferably 2,000 to 100,000. The molecular weight distribution (Mw / Mn) represented by the ratio of Mw to the number average molecular weight (Mn) in terms of polystyrene measured by GPC is preferably 8 or less, more preferably 6 or less. The polymer (P) used for preparing the liquid crystal aligning agent may be one type or a combination of two or more types.

[0071] The content of the polymer (P) in the liquid crystal alignment agent is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 5% by mass or more, based on the total amount of the polymer components contained in the liquid crystal alignment agent. The content of the polymer (P) is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less, based on the total amount of the polymer components contained in the liquid crystal alignment agent. As the polymer (P), one type may be used alone, or two or more types may be used in combination.

[0072] <Other ingredients> The liquid crystal aligning agent of the present disclosure contains the polymer (P) as described above, and may contain other components other than the polymer (P) as necessary.

[0073] (Polymer (Q)) From the viewpoint of further improving electrical properties and reliability, the liquid crystal aligning agent of the present disclosure preferably further contains a polymer (Q) different from the polymer (P).

[0074] Examples of the polymer (Q) include polyamic acid, polyimide, polyamic acid ester, polyamide, polyorganosiloxane, polymers of monomers having unsaturated bonds, etc. From the viewpoints of improving electrical properties, affinity with liquid crystal, mechanical strength, and affinity with the polymer (P), it is particularly preferable that the polymer (Q) is at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.

[0075] From the viewpoint of achieving a well-balanced effect between the incorporation of the polymer (Q) and the incorporation of the polymer (P), the amount of the polymer (Q) contained in the liquid crystal alignment agent is preferably an amount such that the amount of the polymer (P) is 100 parts by mass or more, more preferably an amount of 100 to 2000 parts by mass, and even more preferably an amount of 200 to 1500 parts by mass, per 100 parts by mass of the polymer (Q) used to prepare the liquid crystal alignment agent.

[0076] Polyamic acid, polyamic acid ester and polyimide The polyamic acid, polyamic acid ester, and polyimide contained in the liquid crystal alignment agent can be synthesized according to a conventionally known method. For example, the polyamic acid can be obtained by reacting a tetracarboxylic dianhydride with a diamine. The polyamic acid ester can be obtained by, for example, reacting the polyamic acid obtained above with an esterifying agent (e.g., methanol, ethanol, N,N-dimethylformamide diethyl acetal, etc.). The polyimide can be obtained by, for example, imidizing the polyamic acid obtained above by dehydrating and ring-closing the polyamic acid. The imidization rate of the polyimide is preferably 20 to 95%, more preferably 30 to 90%. This imidization rate is the ratio of the number of imide ring structures to the total number of amic acid structures and the number of imide ring structures of the polyimide, expressed as a percentage.

[0077] The tetracarboxylic dianhydride used in the polymerization is not particularly limited, and various tetracarboxylic dianhydrides can be used. Specific examples thereof include aliphatic tetracarboxylic dianhydrides such as butane tetracarboxylic dianhydride and ethylenediamine tetraacetic dianhydride; 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentyl acetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 2,4,6,8- Alicyclic tetracarboxylic dianhydrides such as tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride, cyclopentanetetracarboxylic dianhydride, and cyclohexanetetracarboxylic dianhydride; aromatic tetracarboxylic dianhydrides such as pyromellitic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, p-phenylene bis(trimellitic monoester anhydride), ethylene glycol bis(anhydrotrimellitate), and 1,3-propylene glycol bis(anhydrotrimellitate); and tetracarboxylic dianhydrides described in JP-A-2010-97188 can be used. The tetracarboxylic dianhydrides may be used alone or in combination of two or more.

[0078] Examples of the diamine used in the polymerization include aliphatic diamines such as ethylenediamine and tetramethylenediamine; alicyclic diamines such as p-cyclohexanediamine and 4,4'-methylenebis(cyclohexylamine); hexadecanoxydiaminobenzene, cholestanyloxydiaminobenzene, cholestanyl diaminobenzoate, cholesteryl diaminobenzoate, lanostannyl diaminobenzoate, 3,6-bis(4-aminobenzoyloxy)cholestane, 3,6-bis(4-aminophenoxy)cholestane, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-butylcyclohexane, 2,5-diamino-N,N-diallylaniline, and compounds represented by the following formulae (2-1) to (2-4): [ka]

[0079] Side-chain aromatic diamines such as compounds represented by the following formulas: p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylamine, 4-aminophenyl-4'-aminobenzoate, 4,4'-diaminoazobenzene, 3,5-diaminobenzoic acid, 1,2-bis(4-aminophenoxy)ethane, 1,5-bis(4-aminophenoxy)pentane, bis[2-(4-aminophenyl)ethyl]hexanedioic acid, bis(4-aminophenyl)amine, N,N-bis(4-aminophenyl)methylamine, N,N'-bis(4-aminophenyl)-benzidine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)- Examples of the diamine include non-side chain aromatic diamines such as 4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-(phenylenediisopropylidene)bisaniline, 1,4-bis(4-aminophenoxy)benzene, 4-(4-aminophenoxycarbonyl)-1-(4-aminophenyl)piperidine, and 4,4'-[4,4'-propane-1,3-diylbis(piperidine-1,4-diyl)]dianiline; and diaminoorganosiloxanes such as 1,3-bis(3-aminopropyl)-tetramethyldisiloxane. In addition, the diamines described in JP-A-2010-97188 can be used. The diamines may be used alone or in combination of two or more.

[0080] As the diamine used in the polymerization, in addition to the above, for example, a photoalignment group-containing diamine, an initiator group-containing diamine, or a nitrogen-containing diamine represented by each of the following formulae (19-1) to (19-10) can be used. [ka]

[0081] The polyamic acid, polyamic acid ester and polyimide contained in the liquid crystal alignment agent preferably have a weight average molecular weight (Mw) in terms of polystyrene measured by GPC of 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn) is preferably 7 or less, more preferably 5 or less. The polyamic acid, polyamic acid ester and polyimide contained in the liquid crystal alignment agent may be one type or a combination of two or more types.

[0082] (Crosslinking agent) The liquid crystal aligning agent of the present disclosure may further contain a crosslinking agent. Examples of the crosslinking agent include compounds having a functional group capable of reacting with a functional group (e.g., an amino group, a carboxyl group, an epoxy group, a polymeric unsaturated bond group, etc.) possessed by the polymer (P) or other polymers. Specific examples of the functional group possessed by the crosslinkable group include a cyclic ether group, a carboxyl group, a cyclic carbonate group, an alcoholic hydroxyl group, a β-hydroxyamide group, an amino group, a protected amino group, a protected isocyanate group, a trialkoxysilyl group, a polymerizable unsaturated bond group, and a maleimide group. The number of crosslinkable groups possessed by the crosslinking agent is preferably 2 or more, more preferably 3 or more, and even more preferably 3 to 6.

[0083] When a crosslinking agent is blended, the content of the crosslinking agent in the liquid crystal alignment agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the total amount of the polymer components in the liquid crystal alignment agent. In addition, from the viewpoint of suppressing the performance degradation caused by the addition of an excessive amount, the content of the crosslinking agent is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, relative to 100 parts by mass of the total amount of the polymer components in the liquid crystal alignment agent. Note that the crosslinking agent can be used alone or in combination of two or more kinds.

[0084] (solvent) The liquid crystal aligning agent is usually prepared as a liquid composition in which the polymer (P) and other components used as necessary are preferably dispersed or dissolved in a suitable solvent.

[0085] Examples of the organic solvent to be used include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,2-dimethyl-2-imidazolidinone, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone (diacetone alcohol), ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, and ethylene glycol-i-propyl ether. Examples of suitable ethers include ethylene glycol n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisopentyl ether, ethylene carbonate, propylene carbonate, etc. These may be used alone or in combination of two or more.

[0086] In addition to the above, other components include, for example, low molecular weight compounds having at least one epoxy group in the molecule and a molecular weight of 1000 or less (e.g., ethylene glycol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, etc.), functional silane compounds, polyfunctional (meth)acrylates, antioxidants, metal chelate compounds, curing accelerators, surfactants, fillers, dispersants, photosensitizers, etc. The blending ratio of the other components can be appropriately selected according to each compound within a range that does not impair the effects of the present disclosure.

[0087] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of the components other than the solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected in consideration of viscosity, volatility, etc., but is preferably in the range of 1 to 10 mass %. That is, the liquid crystal alignment agent is applied to the surface of a substrate as described below, and is preferably heated to form a coating film that is a liquid crystal alignment film or a coating film that will become a liquid crystal alignment film. In this case, if the solid content concentration is 1 mass % or more, the thickness of the coating film can be sufficiently ensured, which is preferable in that a good liquid crystal alignment film can be easily obtained. In addition, if the solid content concentration is 10 mass % or less, the thickness of the coating film does not become too large, and a good liquid crystal alignment film can be obtained, and the viscosity of the liquid crystal alignment agent can be appropriately ensured, and the applicability can be improved.

[0088] <Liquid crystal alignment film and liquid crystal element> The liquid crystal alignment film of the present disclosure is formed by the liquid crystal alignment agent prepared as described above. The liquid crystal element of the present disclosure includes a liquid crystal alignment film formed by using the liquid crystal alignment agent described above. The operation mode of the liquid crystal in the liquid crystal element is not particularly limited, and can be applied to various modes such as TN (Twisted Nematic) type, STN (Super Twisted Nematic) type, VA (Vertical Alignment) type (including VA-MVA type, VA-PVA type, etc.), IPS (In-Plane Switching) type, FFS (Fringe Field Switching) type, OCB (Optically Compensated Bend) type, etc. The liquid crystal element can be manufactured by a method including, for example, the following steps 1 to 3. In step 1, the substrate used differs depending on the desired operation mode. Steps 2 and 3 are common to each operation mode.

[0089] (Step 1: Formation of coating film) First, a liquid crystal alignment agent is applied onto a substrate, and a coating film is formed on the substrate, preferably by heating the applied surface. As the substrate, for example, a transparent substrate made of glass such as float glass or soda glass; or plastic such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, or poly(alicyclic olefin) can be used. As the transparent conductive film provided on one side of the substrate, a NESA film (registered trademark of US PPG) made of tin oxide (SnO2), an ITO film made of indium oxide-tin oxide (In2O3-SnO2), or the like can be used. When manufacturing a TN-type, STN-type, or VA-type liquid crystal element, two substrates on which a patterned transparent conductive film is provided are used. On the other hand, when manufacturing an IPS-type or FFS-type liquid crystal element, a substrate on which an electrode made of a transparent conductive film or a metal film patterned into a comb tooth shape is provided, and an opposing substrate on which no electrode is provided are used. As the metal film, for example, a film made of a metal such as chromium can be used. The liquid crystal alignment agent is applied to the substrate on the surface on which the electrodes are formed, preferably by offset printing, spin coating, roll coating or inkjet printing.

[0090] After the liquid crystal alignment agent is applied, preliminary heating (prebaking) is preferably performed for the purpose of preventing dripping of the applied liquid crystal alignment agent, etc. The prebaking temperature is preferably 30 to 150° C., more preferably 40 to 120° C. The prebaking time is preferably 0.25 to 10 minutes.

[0091] Thereafter, the solvent is further removed, and a baking (post-baking) step is carried out, if necessary, for the purpose of thermally imidizing the amic acid structure present in the polymer. The baking temperature (post-baking temperature) at this time is preferably 250°C or less, more preferably 230°C or less, and even more preferably 180°C or less, from the viewpoint of suppressing deterioration such as discoloration due to high temperatures when forming a liquid crystal alignment film on a color filter, and from the viewpoint of reducing environmental load. In addition, from the viewpoint of suppressing a decrease in liquid crystal alignment property and reliability due to the influence of the solvent component remaining in the film, the post-baking temperature is preferably 80°C or more, more preferably 120°C or more. The post-baking time is preferably 5 to 150 minutes. The film thickness of the film thus formed is preferably 0.001 to 1 μm. After applying the liquid crystal alignment agent on the substrate, the organic solvent is removed to form a liquid crystal alignment film or a coating film that will become a liquid crystal alignment film.

[0092] (Step 2: Orientation Treatment) When a TN-type, STN-type, IPS-type or FFS-type liquid crystal element is manufactured, a treatment (alignment treatment) is carried out to impart liquid crystal alignment ability to the coating film formed in the above step 1. This imparts the alignment ability of liquid crystal molecules to the coating film, forming a liquid crystal alignment film. As the alignment treatment, it is preferable to use a rubbing treatment in which the surface of the coating film formed on the substrate is rubbed with cotton or the like, or a photo-alignment treatment in which the coating film is irradiated with light to impart liquid crystal alignment ability. When a vertical alignment type liquid crystal element is manufactured, the coating film formed in the above step 1 may be used as it is as a liquid crystal alignment film, or the coating film may be subjected to an alignment treatment in order to further enhance the liquid crystal alignment ability.

[0093] The light irradiation in the photo-alignment treatment can be performed by a method of irradiating the coating film after the post-bake step, a method of irradiating the coating film after the pre-bake step but before the post-bake step, or a method of irradiating the coating film during heating in at least one of the pre-bake step and the post-bake step. In the photo-alignment treatment, the radiation to be irradiated to the coating film can be, for example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm. Preferably, ultraviolet light containing light with a wavelength of 200 to 400 nm. When the radiation is polarized, it may be linearly polarized or partially polarized. In addition, when the radiation used is linearly polarized or partially polarized, the radiation may be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When non-polarized radiation is irradiated, the direction of irradiation is an oblique direction.

[0094] Examples of light sources that can be used include low-pressure mercury lamps, high-pressure mercury lamps, deuterium lamps, metal halide lamps, argon resonance lamps, xenon lamps, and excimer lasers. The radiation dose is preferably 400 to 20,000 J / m 2 and more preferably 1,000 to 5,000 J / m 2 The coating film may be irradiated with light while being heated in order to enhance reactivity. The method may further include a step of contacting the organic film that has been subjected to the light irradiation treatment with water, a water-soluble organic solvent, or a mixed solvent of water and a water-soluble organic solvent.

[0095] (Step 3: Construction of liquid crystal cell) Two substrates on which a liquid crystal alignment film is formed are prepared as described above, and a liquid crystal is placed between the two substrates arranged opposite to each other to manufacture a liquid crystal cell. For example, the liquid crystal cell can be manufactured by (1) arranging two substrates opposite to each other with a gap (spacer) between them so that the liquid crystal alignment films face each other, bonding the peripheries of the two substrates together using a sealant, injecting liquid crystal into the substrate surfaces and the cell gap partitioned by the sealant, and then sealing the injection hole, or (2) applying a sealant to a predetermined location on one substrate on which a liquid crystal alignment film is formed, dropping liquid crystal into a few predetermined locations on the liquid crystal alignment film surface, bonding the other substrate so that the liquid crystal alignment film faces each other, and spreading the liquid crystal over the entire surface of the substrate (ODF method). It is preferable to further heat the manufactured liquid crystal cell to a temperature at which the liquid crystal used has an isotropic phase, and then slowly cool it to room temperature to remove the flow alignment that occurs when the liquid crystal is filled.

[0096] The sealing agent may be, for example, an epoxy resin containing a hardener and aluminum oxide spheres as spacers, etc. The spacers may be photospacers, bead spacers, etc.

[0097] The liquid crystal used may be nematic liquid crystal or smectic liquid crystal, among which nematic liquid crystal is preferred. As the nematic liquid crystal, for example, Schiff base liquid crystal, azoxy liquid crystal, biphenyl liquid crystal, phenylcyclohexane liquid crystal, ester liquid crystal, terphenyl liquid crystal, biphenylcyclohexane liquid crystal, pyrimidine liquid crystal, dioxane liquid crystal, bicyclooctane liquid crystal, cubane liquid crystal, etc. may be used. In addition, for example, cholesteric liquid crystal, chiral agent, ferroelectric liquid crystal, etc. may be added to these liquid crystals.

[0098] In the PSA mode, a polymerizable compound (e.g., a polyfunctional (meth)acrylate compound, etc.) is filled into the cell gap together with the liquid crystal, and after the liquid crystal cell is constructed, a process is performed in which the liquid crystal cell is irradiated with light while a voltage is applied between the conductive films of a pair of substrates. In manufacturing a PSA mode liquid crystal element, the proportion of the polymerizable compound used is 0.01 to 3 parts by mass, preferably 0.1 to 1 part by mass, based on 100 parts by mass of the total liquid crystal.

[0099] Next, a polarizing plate is attached to the outer surface of the liquid crystal cell as needed. Examples of polarizing plates include a polarizing film called an "H film" made by absorbing iodine while stretching and aligning polyvinyl alcohol, sandwiched between cellulose acetate protective films, or a polarizing plate made of the H film itself. This produces a liquid crystal element.

[0100] The liquid crystal element of the present disclosure can be effectively applied to various applications. Specifically, it can be used in various display devices such as watches, portable game machines, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays, as well as light control films. In addition, the liquid crystal element formed using the liquid crystal alignment agent of the present disclosure can also be applied to optical films such as retardation films. EXAMPLES

[0101] The present disclosure will be described in more detail below with reference to examples, but the contents of the present disclosure are not limited to the following examples.

[0102] In the following examples, the weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymers were measured by the following methods. <Weight average molecular weight, number average molecular weight and molecular weight distribution> Mw and Mn were measured by gel permeation chromatography (GPC) under the following conditions. The molecular weight distribution (Mw / Mn) was calculated from the obtained Mw and Mn. Equipment: Showa Denko Co., Ltd. "GPC-101" GPC column: Shimadzu GLC's "GPC-KF-801", "GPC-KF-802", "GPC-KF-803" and "GPC-KF-804" combined Mobile phase: Tetrahydrofuran (THF) Column temperature: 40℃ Flow rate: 1.0mL / min Sample concentration: 1.0% by mass Sample injection volume: 100 μL Detector: Differential refractometer Standard material: Monodisperse polystyrene

[0103] The compounds used in the following examples are shown below. For convenience, hereinafter, a "compound represented by formula (X)" may be simply referred to as a "compound (X)".

[0104] (Reactive Compounds) [ka] [ka]

[0105] (Acid anhydride group-containing monomer) [ka]

[0106] (Monomer that gives structural unit U2) [ka]

[0107] (Monomer that gives structural unit U3) [ka]

[0108] (Other monomers) [ka]

[0109] (Tetracarboxylic acid dianhydride) [ka]

[0110] (Diamine) [ka] [ka]

[0111] (Additives) [ka] [ka]

[0112] <Synthesis of Monomer> [Synthesis Example 1-1: Synthesis of compound (E-3)] Compound (E-3) was synthesized according to the following scheme. [ka]

[0113] In a 500 ml three-necked flask containing a stirrer, 15.0 g of tert-butyl 4-(2-hydroxyethyl)benzylcarbamate, 12.0 g of 1-(4-fluorophenyl)-2-hydroxy-2-methylpropan-1-one, 9.1 g of potassium carbonate, and 300 mL of N,N-dimethylformamide were added and stirred at room temperature for 30 minutes. After confirming that the raw materials were dissolved, the mixture was reacted at 80°C for 12 hours. After the reaction, the reaction solution was poured into 1500 ml of distilled water, and the precipitated solid was filtered. The solid was then vacuum dried and recrystallized to obtain 16.7 g of an intermediate. 100 ml of trifluoroacetic acid was added thereto, and the mixture was stirred for 1 hour, then dissolved in a mixed solution of THF / ethyl acetate, and separated twice with sodium bicarbonate and three times with water. The organic layer was evaporated and then dried to obtain 10.5 g of compound (E-3).

[0114] [Synthesis Example 1-2: Synthesis of compound (E-14)] Compound (E-14) was synthesized according to the following scheme. [ka]

[0115] In Synthesis Example 1-1, tert-butyl 4-(2-hydroxyethyl)benzylcarbamate and 1-(4-fluorophenyl)-2-hydroxy-2-methylpropan-1-one were replaced with (4-fluorobenzyl)carbamic acid tert-butyl ester and 4-(4-pentylcyclohexyl)phenol, respectively, and the same method as Synthesis Example 1-1 was used to obtain 9.7g of compound (E-14). Note that (4-fluorobenzyl)carbamic acid tert-butyl ester was synthesized according to the method described in Tetrahedron, 2001, 57, 2965-2972.

[0116] [Synthesis Example 1-3: Synthesis of compound (E-15)] Compound (E-15) was synthesized according to the following scheme. [ka]

[0117] 200 ml of thionyl chloride and catalytic amount of DMF were added to 31.4 g of (E)-3-(4-(4'-pentyl-[1,1'-bi(cyclohexane)]-4-yl)phenyl)acrylic acid, and the mixture was reacted at 60°C for 2 hours. After the reaction, thionyl chloride was distilled off under reduced pressure. The obtained solid was dissolved in 200 ml of dehydrated THF to obtain solution A. On the other hand, 13.2 g (82.0 mmol) of tert-butyl (2-hydroxyethyl)carbamate and 5.00 g of triethylamine were dissolved in 100 ml of dehydrated THF, and the mixture was ice-cooled to 0°C. Solution A was added dropwise thereto, and the mixture was reacted at room temperature overnight. After the reaction, the reaction solution was separated twice with 1N hydrochloric acid and three times with water, and the organic layer was distilled off under reduced pressure to obtain a Boc-protected intermediate. 100 ml of trifluoroacetic acid was added thereto, and the mixture was stirred for 1 hour, then dissolved in a mixed solution of THF / ethyl acetate, and separated twice with sodium bicarbonate and three times with water. The organic layer was evaporated and then dried to obtain compound (E-15).

[0118] [Synthesis Examples 1-4 and 1-5: Synthesis of Compounds (E-16) and (E-17)] The intermediates of compounds (E-16) and (E-17) were synthesized according to the method described in the following document. Compounds (E-16) and (E-17) were obtained by the same method as in Synthesis Example 1-3, except that each intermediate was used instead of (E)-3-(4-(4'-pentyl-[1,1'-bi(cyclohexane)]-4-yl)phenyl)acrylic acid in Synthesis Example 1-3. Compound (E-16) intermediate: Molecular Crystals and Liquid Crystals, 2017, 650, 32-45 Compound (E-17) intermediate: Angewandte Chemie International Edition, 2009, 48, 3494-3498

[0119] [Synthesis Example 1-6: Synthesis of compound (E-18)] [ka]

[0120] 200 ml of a dehydrated THF solution of 30.2 g of triethyl phosphonoacetate was added dropwise to 4.8 g of sodium hydride, and the mixture was stirred at 0°C for 2 hours. 100 ml of a THF solution of 33.7 g of 4-acetylphenyl 4-(4-cyanobutoxy)benzoate was added dropwise thereto, and the mixture was stirred at room temperature for 1 hour, and then reacted for 2 hours under reflux. After the reaction was completed, 300 ml of ethyl acetate was added, and the mixture was separated twice with a saturated NH4Cl solution and three times with water. The organic layer was distilled off the solvent using a rotary evaporator, and then stirred with 300 ml of water and 10 g of sodium hydroxide under reflux for 3 hours. After stirring, the mixture was adjusted to pH=4 with hydrochloric acid, and the precipitated solid was collected by filtration, washed with water, and dried to obtain 30.9 g of an intermediate. Compound (E-18) was obtained in the same manner as in Synthesis Example 1-3, except that the above intermediate was used instead of (E)-3-(4-(4'-pentyl-[1,1'-bi(cyclohexane)]-4-yl)phenyl)acrylic acid β-methylcinnamate in Synthesis Example 1-3.

[0121] [Synthesis Example 1-7: Synthesis of compound (E-20)] Compound (E-20) was synthesized according to the following scheme. [ka]

[0122] In a 500 ml three-neck flask containing a stirrer, 10.0 g of 4-(4-pentylcyclohexyl)phenol, 9.8 g of 1-fluoro-4-nitrobenzene, 6.2 g of potassium carbonate, and 200 ml of N,N-dimethylformamide were added and stirred at room temperature for 30 minutes. After confirming that the raw materials had dissolved, the mixture was reacted at 80°C for 12 hours. After the reaction, the reaction solution was poured into 1500 ml of distilled water, and the precipitated solid was filtered. The solid was then vacuum dried and recrystallized to obtain 15.2 g of an intermediate. Next, 12.0 g of the intermediate, 2.09 g of 5% palladium carbon, 60 ml of tetrahydrofuran, and 60 ml of ethanol were added to a 500 ml three-necked flask containing a stirrer, and then heated to 80°C. 9.81 g of hydrazine monohydrate was added dropwise thereto, and the mixture was heated under reflux for 6 hours. After cooling to room temperature, the filtered solution was reprecipitated with 600 ml of water. The obtained solid was filtered, washed with water, and then vacuum dried to obtain 10.1 g of compound (E-20).

[0123] <Polymer synthesis> [Synthesis Example 2-1] In a 100mL two-neck flask under nitrogen, 20 mol parts of compound (A-1), 30 mol parts of compound (B-1), 10 mol parts of compound (B-2), 30 mol parts of compound (C-1), and 10 mol parts of compound (D-1) were added as polymerization monomers, 2 mol parts of 2,2'-azobis(2,4-dimethylvaleronitrile) as a radical polymerization initiator relative to 100 mol parts of polymerization monomers, and 50 ml of tetrahydrofuran as a solvent were added, and polymerization was carried out at 70°C for 6 hours. The polymerization reaction was carried out with a total mole number of polymerization monomers of 50 mmol. After reprecipitation in n-hexane, the precipitate was filtered and dried in vacuum at room temperature for 8 hours to obtain the target polymer (P-1). The weight average molecular weight Mw measured in terms of polystyrene by GPC was 83,500, and the molecular weight distribution Mw / Mn was 4.26.

[0124] [Synthesis Examples 2-2 to 2-5, 2-10, and 2-11] Polymerization was carried out in the same manner as in Synthesis Example 2-1, except that the types and molar ratios of the polymerization monomers shown in Table 1 were used, to obtain polymers (P-2) to (P-5), (P-10) and (P-11) having the same weight average molecular weight and molecular weight distribution as the polymer (P-1). The total number of moles of the polymerization monomers was 50 mmol, the same as in Synthesis Example 2-1. The values ​​in Table 1 represent the amount [mol %] of each monomer charged with respect to the total monomers used in the synthesis of the polymer.

[0125] [Synthesis Example 2-6] In a 100 ml two-neck flask, 50 mol parts of compound (A-4), 20 mol parts of compound (C-3), and 20 mol parts of compound (D-2) were added as polymerization monomers, 50 ml of dichloromethane as a solvent, and 0.005 mol parts of the second generation Grubbs catalyst as a polymerization catalyst, and polymerized at room temperature for 8 hours. The polymerization reaction was carried out with a total molar number of polymerization monomers of 20 mmol. 100 mol parts of butyl vinyl ether was added as a polymerization terminator, and the mixture was stirred at room temperature for 30 minutes, after which it was reprecipitated in n-hexane. The precipitate was filtered and dried in vacuum at room temperature for 8 hours to obtain the target polymer (P-6). The weight average molecular weight Mw measured in terms of polystyrene by GPC was 100,300, and the molecular weight distribution Mw / Mn was 2.35.

[0126] [Synthesis Example 2-7] Polymerization was carried out in the same manner as in Synthesis Example 2-6, except that the types and molar ratios of the polymerization monomers were as shown in Table 1, to obtain a polymer (P-7) having a weight average molecular weight and molecular weight distribution equivalent to those of the polymer (P-6). The total number of moles of the polymerization monomers was 20 mmol, the same as in Synthesis Example 2-6.

[0127] [Synthesis Example 2-8] Under nitrogen, 70 mol parts of compound (A-6) and 30 mol parts of compound (B-4) as polymerization monomers, 50 ml of toluene as a solvent, 0.2 micromol parts of bis(cyclopentadienyl)zirconium dichloride as a polymerization catalyst, and 0.003 mol parts of methylaluminoxane were added to a 100 ml two-neck flask, and polymerization was carried out at room temperature for 1 hour. The polymerization reaction was carried out with a total molar number of polymerization monomers of 50 mmol. After reprecipitation in an acidic methanol solution, the precipitate was dissolved in NMP and reprecipitated again in an acidic methanol solution. The target polymer (P-8) was obtained by vacuum drying at room temperature for 8 hours. The weight average molecular weight Mw measured in terms of polystyrene by GPC was 111,200, and the molecular weight distribution Mw / Mn was 3.12.

[0128] [Synthesis Example 2-9] Polymerization was carried out in the same manner as in Synthesis Example 2-8, except that the types and molar ratios of the polymerization monomers were as shown in Table 1, to obtain a polymer (P-9) having a weight average molecular weight and molecular weight distribution equivalent to those of the polymer (P-8). The total number of moles of the polymerization monomers was 50 mmol, the same as in Synthesis Example 2-8.

[0129] [Table 1]

[0130] [Synthesis Example 3-1] To the polymer (P-1) obtained by the above synthesis example 2-1, 10 molar parts of compound (E-1) based on the total amount of monomers charged, and 10 molar parts of compound (E-14) based on the total amount of monomers charged were added. Then, 30 molar parts of dimethylformamide dimethylacetal (DMF-DMA) was added as an esterification agent, and the mixture was heated at 60°C for 3 hours. After that, the obtained solution was reprecipitated with water to obtain the desired polymer (P-12).

[0131] [Synthesis Examples 3-2 to 3-15] Polymerization was carried out in the same manner as in Synthesis Example 3-1, except that the polymer (base resin) to be reacted with the reactive compound and the reactive compound were of the types and molar ratios shown in Table 2, to obtain polymers (P-13) to (P-26) having the same weight average molecular weight and molecular weight distribution as polymer (P-12).

[0132] [Synthesis Examples 3-16 and 3-17] Polymerization was carried out in the same manner as in Synthesis Example 3-1, except that the polymer (base resin) to be reacted with the reactive compound and the reactive compound were of the types and molar ratios shown in Table 2, and that the esterification reaction using an esterifying agent was not carried out, to obtain polymers (P-27) and (P-28) having weight average molecular weights and molecular weight distributions equivalent to those of polymer (P-12).

[0133] [Table 2]

[0134] [Synthesis Example 4-1] 100 mol parts of compound (TA-1) as tetracarboxylic dianhydride, 30 mol parts of compound (DA-1), 50 mol parts of compound (DA-8), and 20 mol parts of compound (DA-9) as diamines were dissolved in 170 g of N-methyl-2-pyrrolidone (NMP) and reacted at 40 ° C for 24 hours to obtain a solution containing 20 mass % of polyamic acid. Next, NMP was added to the obtained polyamic acid solution, and pyridine and acetic anhydride were added in 1.80 molar equivalents each relative to the carboxyl group derived from the tetracarboxylic dianhydride possessed by the polyamic acid, and a dehydration ring-closing reaction was carried out at 80 ° C for 4 hours. After the dehydration ring-closing reaction, the solvent in the system was replaced with fresh NMP and further concentrated to obtain a solution containing 15 mass % of polyimide with an imidization rate of 70% (this is referred to as polymer (PI-1)). A small amount of this solution was taken and NMP was added to make a 10% by mass solution, and the solution viscosity was measured to be 43.7 mPa·s. The resulting polymer solution was then poured into a large excess of methanol to precipitate the reaction product, which was then washed with methanol and dried at 40°C under reduced pressure for 15 hours to obtain polyimide (PI-1).

[0135] [Synthesis Examples 4-2, 4-3, 4-5 to 4-7] Polymerization was performed in the same manner as in Synthesis Example 4-1, except that the types and amounts of tetracarboxylic dianhydrides and diamines used in polymerization were changed as shown in Table 3, to obtain polyimide polymers (PI-2), (PI-3), (PI-5) to (PI-7). In Table 3, the values ​​of tetracarboxylic dianhydrides represent the ratio (molar parts) of each compound to 100 parts by mole of the total amount of tetracarboxylic dianhydrides used in the synthesis. The values ​​of diamines represent the ratio (molar parts) of each compound to 100 parts by mole of the total amount of diamines used in the synthesis.

[0136] [Synthesis Example 4-4] 100 parts by mole of compound (TA-1) as a tetracarboxylic dianhydride, and 30 parts by mole of compound (DA-1), 50 parts by mole of compound (DA-3), and 20 parts by mole of compound (DA-9) as diamines were dissolved in 170 g of NMP and reacted at 60°C for 8 hours to obtain a solution containing 20% ​​by mass of polyamic acid. The viscosity of this solution was 707 mPa s.

[0137] Synthesis Examples 4-8, 4-9] Polymerization was carried out in the same manner as in Synthesis Example 4-4, except that the types and amounts of tetracarboxylic dianhydrides and diamines used in polymerization were changed as shown in Table 3, to obtain polyamic acids (PI-8) and (PI-9), respectively.

[0138] [Table 3]

[0139] [Example 1: PSA type liquid crystal display element] (1) Preparation of liquid crystal alignment agent (AL-1) 100 parts by mass of the polymer (PI-1) obtained in Synthesis Example 4-1, 10 parts by mass of the polymer (P-12) obtained in Synthesis Example 3-1, and NMP and BC as solvents were added to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0 mass%. The solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-1).

[0140] (2) Preparation of Liquid Crystal Composition 5% by mass of a liquid crystal compound represented by the following formula (L1-1) and 0.3% by mass of a photopolymerizable compound represented by the following formula (L2-1) were added to 10 g of nematic liquid crystal (MLC-6608, manufactured by Merck) and mixed to obtain liquid crystal composition LC1. [ka]

[0141] (3) Manufacture of PSA type liquid crystal display elements The liquid crystal alignment agent (AL-1) prepared above was applied to each electrode surface of two glass substrates each having a conductive film made of an ITO electrode patterned in a slit shape, using a liquid crystal alignment film printer (manufactured by Nissha Printing Co., Ltd.), heated (pre-baked) for 2 minutes on a hot plate at 80°C to remove the solvent, and then heated (post-baked) for 30 minutes on a hot plate at 230°C to form a coating film with an average thickness of 100 nm. These coating films were ultrasonically cleaned in ultrapure water for 1 minute, and then dried in a clean oven at 100°C for 10 minutes to obtain a pair (2 sheets) of substrates having a liquid crystal alignment film. The electrode pattern used was the same type of pattern as the electrode pattern in the PSA mode. Next, an epoxy resin adhesive containing aluminum oxide spheres with a diameter of 5.5 μm was applied to the outer edge of the surface having the liquid crystal alignment film of one of the pair of substrates, and the substrates were then overlapped with the liquid crystal alignment film surfaces facing each other and pressed together, and the adhesive was cured. Next, the liquid crystal composition LC1 prepared above was filled between the pair of substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an acrylic photocurable adhesive to produce a liquid crystal cell. Then, an AC voltage of 10 V with a frequency of 60 Hz was applied between the conductive films of the liquid crystal cell, and while the liquid crystal was driven, an ultraviolet irradiation device using a metal halide lamp as a light source was used to irradiate the liquid crystal with 100,000 J / m 2 The substrate was irradiated with ultraviolet light at an exposure dose of 100 nm. The exposure dose was measured using an actinometer measuring at a wavelength of 365 nm. After that, polarizing plates were attached to both outer surfaces of the substrate so that the polarization directions of the plates were perpendicular to each other and formed an angle of 45° with the projection direction of the optical axis of the ultraviolet light of the liquid crystal alignment film onto the substrate surface, thereby producing a PSA type liquid crystal display element.

[0142] (4) Evaluation of electrical characteristics by voltage holding ratio (VHR) A voltage of 5V was applied to the PSA type liquid crystal display element manufactured as above for a time of 60 microseconds over a span of 167 milliseconds, and the voltage retention rate was measured 167 milliseconds after the application was removed. A VHR-1 manufactured by Toyo Corporation was used as the measuring device. At this time, a voltage retention rate of 98% or more was rated as "good (○)", 95% or more but less than 98% was rated as "passable (△)", and less than 95% was rated as "poor (×)". As a result, in this example, the electrical characteristics were rated as "good (○)".

[0143] (5) Evaluation of electrical characteristics by VHR after long-term baking A PSA type liquid crystal display element was fabricated in the same manner as in (3) above, except that the post-bake time was changed from 30 minutes to 1.5 hours. The voltage retention rate of this fabricated PSA type liquid crystal display element was measured under the same conditions as in (4) above. At this time, a voltage retention rate of 95% or more was rated "good (○)", a rate of 90% or more but less than 95% was rated "fair (△)", and a rate of less than 90% was rated "poor (×)". It can be said that the higher the VHR after long-term baking, the less likely impurities are to be generated by post-bake. As a result, in this example, the electrical characteristics after long-term baking were rated "good (○)".

[0144] (6) Evaluation of long-term heat resistance A PSA type liquid crystal cell was manufactured by the same operation as in (3) above, except that no polarizing plate was attached to both outer sides of the substrate. The voltage retention rate was measured for this PSA type liquid crystal cell by the same operation as in (4) above. In addition, the obtained liquid crystal cell was stored in a thermostatic chamber at 100°C for 21 days (about 500 hours), and then the voltage retention rate was measured again. When the decrease in the voltage retention rate due to storage in a thermostatic chamber at 100°C (voltage retention rate (%) after liquid crystal cell production - voltage retention rate (%) after storage in a thermostatic chamber) was less than 10%, it was rated as "excellent (◎)", when it was 10% or more and less than 20%, it was rated as "good (○)", when it was 20% or more and less than 40%, it was rated as "fair (△)", and when it was 40% or more, it was rated as "poor (×)". As a result, in this example, it was rated as "good (○)".

[0145] (7) Evaluation of AC image retention characteristics (thin film evaluation) A PSA type liquid crystal cell was prepared in the same manner as in (3) above, except that the average thickness of the coating film was changed from 100 nm to 30 nm, and no polarizing plate was attached to both outer sides of the substrate. The prepared liquid crystal cell was measured by a rotational crystal method using a He-Ne laser beam in accordance with the method described in "TJ Scheffer et.al., J.Appl.Phys.vol.48,p1783(1977)" and "F.Nakano,et.al.,JPN.J.Appl.Phys.vol.19,p2013(1980)". The pretilt angle before applying a voltage to the liquid crystal cell (initial pretilt angle θini) and the pretilt angle after driving at AC9V and room temperature for 30 hours (pretilt angle after driving θac) were measured. The pretilt angle change rate β [%] was calculated by the following formula (y). A pretilt angle change rate β of less than 3% was evaluated as "good (◯)", a rate of 3% or more and less than 5% was evaluated as "fair (△)", and a rate of 5% or more was evaluated as "poor (×)". Pretilt angle change rate β[%]=(θac-θini) / θini×100 …(y)

[0146] [Examples 2 to 7, 9, 10, and 15 and Comparative Examples 1 to 3] Liquid crystal alignment agents (AL-2) to (AL-7), (AL-9), (AL-10), (AL-15) to (AL-18) were prepared with the same solvent composition and solid content concentration as in Example 1, except that the blending composition was changed as shown in Table 4. In addition, using each liquid crystal alignment agent, PSA type liquid crystal display elements were manufactured in the same manner as in Example 1, and various evaluations were performed. The evaluation results are shown in Table 4.

[0147] [Example 8: Optical vertical type liquid crystal display element] (1) Preparation of liquid crystal alignment agent 100 parts by mass of the polymer (PI-8) obtained in Synthesis Example 4-8, 10 parts by mass of the polymer (P-19) obtained in Synthesis Example 3-8, 5 parts by mass of the compound (Add-5), and NMP and BC as solvents were added to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0 mass%. The solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-8).

[0148] (2) Manufacturing of vertical optical liquid crystal display elements The liquid crystal alignment agent (AL-8) prepared in (1) above was applied to the transparent electrode surface of a glass substrate with a transparent electrode made of an ITO film using a spinner, prebaked on a hot plate at 80°C for 1 minute, and then baked at 200°C for 40 minutes to form a coating film with a thickness of 0.08 μm. Next, the surface of this coating film was irradiated with 200 J / m of polarized ultraviolet light including a 313 nm emission line using a Hg-Xe lamp and a Glan-Taylor prism. 2 The liquid crystal alignment film was formed on the substrate by repeating the same procedure at room temperature. An epoxy resin adhesive containing aluminum oxide spheres having a diameter of 3.5 μm was applied by screen printing to the outer circumference of the surface having the liquid crystal alignment film of one of the two substrates on which the liquid crystal alignment film was formed, and then the liquid crystal alignment film surfaces of the pair of substrates were placed opposite each other, and the pair of substrates were pressed together so that the projection directions of the optical axis of the ultraviolet light irradiated on each substrate on the substrate surface were antiparallel, and the adhesive was thermally cured at 150°C for 1 hour. Next, a liquid crystal composition (MLC-6608, manufactured by Merck) was filled into the gap between the substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an epoxy adhesive to obtain a liquid crystal cell. Furthermore, in order to remove the flow alignment during liquid crystal injection, the liquid crystal cell was heated at 150°C and then slowly cooled to room temperature. Next, polarizing plates were attached to both outer surfaces of the substrates in the liquid crystal cell so that the polarization directions of the polarizing plates were perpendicular to each other and formed an angle of 45° with the projection direction of the optical axis of the ultraviolet light irradiated during the formation of the liquid crystal alignment film on the substrate surface, thereby producing a vertical light type liquid crystal display element.

[0149] (3) Evaluation The electrical characteristics of the vertical optical type liquid crystal display element (2) were evaluated by voltage holding ratio (VHR) in the same manner as in Example 1. In addition, the electrical characteristics were evaluated by VHR after long-term baking, the long-term heat resistance was evaluated, and the AC afterimage characteristics (thin film evaluation) were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 4.

[0150] [Examples 11 to 13] Liquid crystal alignment agents (AL-11) to (AL-13) were prepared with the same solvent composition and solid content concentration as in Example 8, except that the blending composition was changed as shown in Table 4. In addition, using each liquid crystal alignment agent, a light vertical type liquid crystal display element and a light vertical type liquid crystal cell were manufactured in the same manner as in Example 8, and various evaluations were performed. The evaluation results are shown in Table 4.

[0151] [Example 14: Photo-aligned FFS-type liquid crystal display element] (1) Preparation of liquid crystal alignment agent (AL-14) 100 parts by mass of the polymer (PI-8) obtained in Synthesis Example 4-8, 10 parts by mass of the polymer (P-25) obtained in Synthesis Example 3-14, 5 parts by mass of the compound (Add-9), and NMP and BC as solvents were added to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0 mass%. The solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-14).

[0152] (2) Manufacturing of optical FFS type liquid crystal display elements A glass substrate (first substrate) having a flat electrode (bottom electrode), an insulating layer, and a comb-shaped electrode (top electrode) laminated in this order on one side thereof, and a glass substrate (second substrate) without an electrode were prepared. Next, a liquid crystal alignment agent (AL-14) was applied to the electrode-forming surface of the first substrate and one substrate surface of the second substrate, respectively, using a spinner, and heated (pre-baked) on a hot plate at 80°C for 1 minute. Thereafter, the substrate was dried (post-baked) for 30 minutes in an oven at 230°C with the interior replaced with nitrogen, forming a coating film with an average thickness of 0.1 μm. The obtained coating film was irradiated with 1,000 J / m2 of linearly polarized ultraviolet light containing a 254 nm emission line using a Hg-Xe lamp. 2 The coating film was irradiated with light from the normal direction of the substrate to perform a photo-alignment treatment. The amount of irradiation was measured using an actinometer that measures at a wavelength of 254 nm. Next, the coating film that had been subjected to the photo-alignment treatment was heated in a clean oven at 230°C for 30 minutes to perform a heat treatment, thereby forming a liquid crystal alignment film. Next, for one of the pair of substrates on which the liquid crystal alignment film was formed, an epoxy resin adhesive containing aluminum oxide spheres with a diameter of 3.5 μm was applied by screen printing to the outer edge of the surface having the liquid crystal alignment film. Then, the substrates were overlapped and pressed together so that the projection direction of the polarization axis on the substrate surface during light irradiation was antiparallel, and the adhesive was thermally cured at 150°C for 1 hour. Next, negative liquid crystal (MLC-6608, manufactured by Merck) was filled between the pair of substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an epoxy adhesive to obtain a liquid crystal cell. Furthermore, in order to remove the flow alignment during liquid crystal injection, the liquid crystal cell was heated at 120°C and then slowly cooled to room temperature. Then, polarizing plates were attached to both outer surfaces of the substrate in the liquid crystal cell to obtain a liquid crystal display element. In addition, the above series of operations was performed with a UV irradiation dose of 100 to 10,000 J / m after post-baking. 2 Three or more liquid crystal display elements with different amounts of ultraviolet light irradiation were manufactured by changing the amount of exposure within the range of 1, and the liquid crystal display element with the exposure amount (optimum exposure amount) that showed the best alignment characteristics was used for the following evaluation.

[0153] (3) Evaluation For the optical FFS type liquid crystal display element (2) above, the electrical characteristics were evaluated by voltage holding ratio (VHR), the electrical characteristics were evaluated by VHR after long-term baking, and the long-term heat resistance was evaluated in the same manner as in Example 1. In addition, the AC afterimage characteristics were evaluated (thin film evaluation) by the following procedure. The evaluation results are shown in Table 4.

[0154] Evaluation of AC image retention characteristics of optical FFS type liquid crystal cells (thin film evaluation) An optical FFS type liquid crystal cell was fabricated in the same manner as in (2) above, except that the average thickness of the coating film was changed from 100 nm to 30 nm, and no polarizing plates were attached to both outer sides of the substrate. After driving the optical FFS type liquid crystal cell for 30 hours by applying an AC voltage of 10 V, the black brightness change rate (%) expressed by the following formula (b) was measured using an apparatus in which a polarizer and an analyzer were placed between the light source and the light amount detector. Black luminance change rate (%) = [(β(30hr)-β(0)) / β(0)] × 100 … (b) (In formula (b), β(0) is the minimum light transmittance when the liquid crystal display element is sandwiched between a polarizer and an analyzer under crossed Nicols conditions before driving stress. β(30hr) is the minimum light transmittance when the liquid crystal display element is sandwiched between a polarizer and an analyzer under crossed Nicols conditions after driving for 30 hours.) The AC image retention characteristic is expressed by the rate of change between the black level before and after driving with AC voltage for 30 hours, and the smaller the rate of change, the better the AC image retention characteristic. A black luminance change rate of less than 10% was rated "good (○)", between 10% and 30% was rated "passable (△)", and 30% or more was rated "poor (×)". As a result, the black luminance change rate of this LCD element was 5%, and the AC image retention characteristic was judged to be "good (○)".

[0155] [Table 4]

[0156] As can be seen from the results of the above examples, the liquid crystal alignment agents of Examples 1 to 16 containing the polymer (P) were evaluated as good or excellent in terms of voltage retention rate after long-term baking and long-term heat resistance. In addition, the liquid crystal alignment agents of Examples 1 to 16 were evaluated as good or fair in terms of AC image retention characteristics. In particular, Examples 1 to 15 containing the polymer (P) that had been subjected to esterification treatment had good and excellent AC image retention characteristics.

[0157] In contrast, the liquid crystal alignment agent of Comparative Example 1, which does not contain the polymer (P), was evaluated as acceptable (△) for the voltage holding ratio and long-term heat resistance after long-term baking. The liquid crystal alignment agent of Comparative Example 2 was evaluated as poor (×) for long-term heat resistance and AC afterimage characteristics, and was inferior in performance to Examples 1 to 16. In Comparative Example 2, a polymer (P-11) synthesized using compounds (D-3) and (D-4), which are ring-opened maleimide compounds, was used as a polymer component of the liquid crystal alignment agent. In this polymer (P-11), two groups bonded to the carbon-carbon double bonds of compounds (D-3) and (D-4) have a trans structure, so that it is difficult to close the ring during post-baking, and it is presumed that this is why the evaluations of the voltage holding ratio, long-term heat resistance, and AC afterimage after long-term baking were inferior to Examples 1 to 16.

Claims

1. The polymer (P) contains at least one selected from the group consisting of a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), a structural unit represented by the following formula (3), a structural unit represented by the following formula (4), and a structural unit represented by the following formula (5), The polymer (P) is a liquid crystal aligning agent, which contains a structural unit having a cyclic carbonate structure. 【Chemistry 1】 (In formulas (1) to (5), X 1 and X 2 one of which is a monovalent group represented by the following formula (6), and the other is -OR 4 It is. 4 A is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. m is 1 or 2. "*1" represents a bond bonded to an atom constituting the main chain of the polymer. 【Chemistry 2】 (In formula (6), R 1 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 2 is an alkanediyl group. 3 is a monovalent organic group having one or more carbon atoms. "*" represents a bond.)

2. The R 3 The liquid crystal aligning agent according to claim 1, which has at least one selected from the group consisting of a basic group, a group that generates a basic group when heated, an acidic group, a group that generates an acidic group when heated, a crosslinkable group, a group that generates a crosslinkable group when heated, a photoalignable group, a vertically alignable group, a photoinitiator group, an electron transport group, and a hole transport group.

3. The polymer (P) is —COOR 5 (However, R 5 The liquid crystal aligning agent according to claim 1 or 2, comprising a structural unit having a structure having a monovalent thermally detachable group.

4. The polymer (P) includes a structural unit derived from a monomer selected from the group consisting of a compound represented by the following formula (8-1), a compound represented by the following formula (8-2), an N-substituted aromatic maleimide compound, an olefin-based hydrocarbon, and a (meth)acrylic compound that generates an isocyanate group by heating. The liquid crystal aligning agent according to any one of claims 1 to 3. 【Chemistry 3】 (In formula (8-1), R 18 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. 1 R is a divalent aromatic ring group. 19 is a hydrogen atom or a monovalent organic group. 6 is a monovalent substituent. t is an integer from 0 to 3. r is 0 or 1.

5. The liquid crystal aligning agent according to any one of claims 1 to 4, further comprising at least one polymer selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.

6. A liquid crystal alignment film formed by using the liquid crystal aligning agent according to any one of claims 1 to 5.

7. A liquid crystal element comprising the liquid crystal alignment film according to claim 6.

8. A polymer having at least one selected from the group consisting of a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), a structural unit represented by the following formula (3), a structural unit represented by the following formula (4), and a structural unit represented by the following formula (5), and a structural unit having a cyclic carbonate structure. 【Chemistry 4】 (In formulas (1) to (5), X 1 and X 2 one of which is a monovalent group represented by the following formula (6), and the other is -OR 4 It is. 4 A is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 1 is a methylene group, an ethylene group, a sulfur atom, or an oxygen atom. m is 1 or 2. "*1" represents a bond bonded to an atom constituting the main chain of the polymer. 【Chemistry 5】 (In formula (6), R 1 R is a hydrogen atom or a monovalent organic group having one or more carbon atoms. 2 is an alkanediyl group. 3 is a monovalent organic group having one or more carbon atoms. "*" represents a bond.)

Citation Information

Patent Citations

  • Photoalignment material and the synthetic method thereof

    KR1020150138548A

  • Polymer composition, liquid crystal alignment agent, liquid crystal alignment film, substrate comprising said liquid crystal alignment film, and liquid crystal display element comprising said liquid crystal alignment film

    WO2016186190A1

  • Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal element

    WO2018074547A1

  • Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal element, and production method for liquid crystal element

    WO2019193854A1

  • Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal element, polymer and compound

    WO2019202853A1